Superfoods: exploring sustainability perspectives between nutrient synthesizers and accumulators - G. Santunione; G. Montevecchi; G. Montevecchi (Frontiers in Food Science and Technology)
“Superfoods” is a marketing term used to describe nutrient-dense foods claimed to have health benefits due to their high concentrations of essential amino acids, vitamins, minerals, antioxidants, and other bioactive compounds. Recently, the need for healthy diets has led to increased demand for these functional foods, which have become popular among middle- and high-income groups in developed regions of the earth. Superfoods can represent a smart way to improve diets, particularly in relation to diet-related issues. However, the superfood production system, as well as the broader food production system, must be reconsidered to avoid overexploitation of soil, workers, and natural resources. This perspective explores sustainability of “superfoods” by proposing a new classification system, dividing them into “synthesizers” and “accumulators” based on their origin. The aim is to provide a framework for identifying and promoting superfoods that align with environmental and social sustainability goals, helping guide both consumers and producers toward more responsible choices in food systems. Analyzing the sources and characteristics of the main compounds found in superfoods reveals that most of them come from plants or bacteria, rather than animal origins. Since animal-based food production is one of the largest contributors to greenhouse gas emissions in the agro-food sector and a major driver of deforestation and water use, it is advisable to focus on plant organisms as the primary and direct sources of beneficial compounds. Nevertheless, great attention must be paid to vegetable crops that imply an overexploitation of soil and water and induce the degradation of entire ecosystems.